1998
DOI: 10.1359/jbmr.1998.13.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Girls with Forearm Fractures

Abstract: In childhood, the most common site of fracture is the distal forearm. To determine whether young girls with these fractures have low bone density more commonly than fracture-free controls, we measured bone density at the radius, spine, hip, and whole body and total body bone mineral content, lean tissue mass, and fat mass by dualenergy X-ray absorptiometry in 100 Caucasian girls aged 3-15 years with recent distal forearm fractures and 100 age-and gender-matched controls. Bone density (age-adjusted ratios of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
248
3
10

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(276 citation statements)
references
References 41 publications
9
248
3
10
Order By: Relevance
“…(30,31) Larger case-control studies in both girls and boys (3 to 19 years of age) indicated that prevalent distal forearm fractures are associated with significantly lower BMC and aBMD values at the radius but also at the lumbar spine and hip compared with age-matched controls. (6,32) In prospective cohorts of young girls, low areal bone mass was a risk for incident fracture, and the observed low bone mass was found to persist after puberty. (33,34) Moreover, in girls with childhood fractures, a lower BMC, smaller bone area, and smaller bone width as assessed by DXA were observed after puberty (16 years of age) but also prior to menarche (9 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…(30,31) Larger case-control studies in both girls and boys (3 to 19 years of age) indicated that prevalent distal forearm fractures are associated with significantly lower BMC and aBMD values at the radius but also at the lumbar spine and hip compared with age-matched controls. (6,32) In prospective cohorts of young girls, low areal bone mass was a risk for incident fracture, and the observed low bone mass was found to persist after puberty. (33,34) Moreover, in girls with childhood fractures, a lower BMC, smaller bone area, and smaller bone width as assessed by DXA were observed after puberty (16 years of age) but also prior to menarche (9 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the DXA BMD of normal children and adolescents with forearm fractures to that of age-matched controls without fractures. Most [35][36][37][38][39], but not all [40,41], found that mean DXA BMD was significantly lower in children with forearm fractures than in controls.…”
Section: Skeletal Modeling During Growth and Developmentmentioning
confidence: 91%
“…In spite of this, our fracture cases had lower bone mass and bone area density throughout their skeletons than fracture-free controls, and we suggested that a low bone mineral content relative to body weight might make overweight children vulnerable to fragility fractures. 7,8 Others report low bone density in the spine and radius of overweight children 9 ± 11 and orthopaedic problems such as slipped capital epiphyses of the femora, 12 scoliosis and tibia varu 13 are recognized health risks of childhood obesity.…”
Section: Introductionmentioning
confidence: 99%